2019
DOI: 10.1016/j.trf.2019.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Modelling visual-vestibular integration and behavioural adaptation in the driving simulator

Abstract: It is well established that not only vision but also other sensory modalities affect drivers' control of their vehicles, and that drivers adapt over time to persistent changes in sensory cues (for example in driving simulators), but the mechanisms underlying these behavioural phenomena are poorly understood. Here, we consider the existing literature on how driver steering in slalom tasks is affected by the down-scaling of vestibular cues, and propose a driver model that can explain the empirically observed eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The original designers of the framework used it to implement a steering control model [7], adapting the continuous steering model of Salvucci and Gray [10]. In a subsequent study, they also demonstrated that non-visual cues could be integrated into their framework, showing that vestibular cues have an important role in driver control in slalom tasks [11]. The present paper is the first attempt to extend this framework to model driver control in crossing scenarios.…”
Section: Introductionmentioning
confidence: 89%
“…The original designers of the framework used it to implement a steering control model [7], adapting the continuous steering model of Salvucci and Gray [10]. In a subsequent study, they also demonstrated that non-visual cues could be integrated into their framework, showing that vestibular cues have an important role in driver control in slalom tasks [11]. The present paper is the first attempt to extend this framework to model driver control in crossing scenarios.…”
Section: Introductionmentioning
confidence: 89%
“…A representation of the inner ear organs is depicted in Fig.1. An example of modelling the visual-vestibular system was presented in [16], showing how drivers make use of the vestibular system to determine steering angle. Furthermore, this work provides evidence that drivers adapt depending on how those cues are given.…”
Section: Human Perceptual Systemmentioning
confidence: 99%
“…The desired path yaw rate error (DPYRE) model was used to assess the driver's performance [21,22]. It uses three parameters (delay time, preview time and gain) presented in Equation 1, and the reference trajectory to predict the driver behaviour (steering rate).…”
Section: Objective Measuresmentioning
confidence: 99%